Shear‐Velocity Structure and Dynamics Beneath the Sicily Channel and Surrounding Regions of the Central Mediterranean Inferred From Seismic Surface Waves. (13th October 2022) - Agius, M. R.; Magrini, F.; Diaferia, G.; Kästle, E. D.; Cammarano, F.; Faccenna, C.; Funiciello, F.; van der Meijde, M.
Abstract: The evolution of the Sicily Channel Rift Zone (SCRZ) is thought to accommodate the regional tectonic stresses of the Calabrian subduction system. Much of the observations we have today are either limited to the surface or to the upper crust or deeper from regional seismic tomography, missing important details about the lithospheric structure and dynamics. It is unclear whether the rifting is passive from far‐field extensional stresses or active from mantle upwelling beneath. We measure Rayleigh‐and Love‐wave phase velocities from ambient seismic noise and invert for 3‐D shear‐velocity and radial anisotropic models. Variations in crustal S‐velocities coincide with topographic and tectonic features. The Tyrrhenian Sea has a ∼10 km thin crust, followed by the SCRZ (∼20 km). The thickest crust is beneath the Apennine‐Maghrebian Mountains (∼55 km). Areas experiencing extension and intraplate volcanism have positive crustal radial anisotropy ( V SH > V SV ); areas experiencing compression and subduction‐related volcanism have negative anisotropy. The crustal anisotropy across the Channel shows the extent of the extension. Beneath the Tyrrhenian Sea, we find very low sub‐Moho S‐velocities. In contrast, the SCRZ has a thin mantle lithosphere underlain by a low‐velocity zone. The lithosphere‐asthenosphere boundary rises from 60 km depth beneath Tunisia to ∼33 km beneath the SCRZ. Negative radial anisotropy in the upper mantle beneath the SCRZ is consistent with vertical mantle flow. We hypothesize a more active mantle upwelling beneath the rift than previously thought from an interplay between poloidal and toroidal fluxes related to the Calabrian slab, which in turn produces uplift at the surface and induces volcanism. Plain Language Summary: The Calabrian arc system in the central Mediterranean is undergoing multiple tectonic processes of subduction and lithospheric extension. Various models explain the evolution of this complex system but lack detail on the extension and rifting along the arc, particularly across the Sicily Channel. We use seismic data from 83 stations to image the seismic velocity of the lithosphere and asthenosphere below the region in high resolution. We map areas experiencing extension and compression and observe that these coincide with active seismicity and volcanism. We find that the Sicily Channel has a thinner than average crust, a thin mantle lithospheric lid, and is underlain by a low shear‐velocity zone. Polarized shear velocities suggest mantle upwelling beneath the rift that produces uplift at the surface and induces volcanism. Our results provide new constraints on the evolution of the Calabrian slab and on the interplay between poloidal and toroidal fluxes of subduction zones. Key Points: Positive seismic radial anisotropy highlights the extent of rifting across the Sicily Channel The lithosphere beneath the Sicily Channel Rift Zone is thin, underlain by low seismic shear velocities and negative radial anisotropy Negative radial anisotropy in the upper mantle beneath the Sicily Channel suggests upwelling from slab‐related poloidal flow